Climatologies and long-term changes in mesospheric wind and wave measurements based on radar observations at high and mid latitudes - S. Wilhelm; G. Stober; P. Brown (Annales Geophysicae, 2019)
We report on long-term observations of atmospheric parameters in the mesosphere and lower thermosphere (MLT) made over the last 2 decades. Within this study, we show, based on meteor wind measurement, the long-term variability of winds, tides, and kinetic energy of planetary and gravity waves. These measurements were done between the years 2002 and 2018 for the high-latitude location of Andenes (69.3 ∘ N, 16 ∘ E) and the mid-latitude locations of Juliusruh (54.6 ∘ N, 13.4 ∘ E) and Tavistock (43.3 ∘ N, 80.8 ∘ W). While the climatologies for each location show a similar pattern, the locations differ strongly with respect to the altitude and season of several parameters. Our results show annual wind tendencies for Andenes which are toward the south and to the west, with changes of up to 3 m s −1 per decade, while the mid-latitude locations show smaller opposite tendencies to negligible changes. The diurnal tides show nearly no significant long-term changes, while changes for the semidiurnal tides differ regarding altitude. Andenes shows only during winter a tidal weakening above 90 km , while for the Canadian Meteor Orbit Radar (CMOR) an enhancement of the semidiurnal tides during the winter and a weakening during fall occur. Furthermore, the kinetic energy for planetary waves showed strong peak values during winters which also featured the occurrence of sudden stratospheric warming. The influence of the 11-year solar cycle on the winds and tides is presented. The amplitudes of the mean winds exhibit a significant amplitude response for the zonal component below 82 km during summer and from November to December between 84 and 95 km at Andenes and CMOR. The semidiurnal tides (SDTs) show a clear 11-year response at all locations, from October to November.